2018
DOI: 10.1038/s41398-018-0104-z
|View full text |Cite
|
Sign up to set email alerts
|

Altered brainstem responses to modafinil in schizophrenia: implications for adjunctive treatment of cognition

Abstract: Candidate pro-cognitive drugs for schizophrenia targeting several neurochemical systems have consistently failed to demonstrate robust efficacy. It remains untested whether concurrent antipsychotic medications exert pharmacodynamic interactions that mitigate pro-cognitive action in patients. We used functional MRI (fMRI) in a randomized, double-blind, placebo-controlled within-subject crossover test of single-dose modafinil effects in 27 medicated schizophrenia patients, interrogating brainstem regions where c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…However, both the executive control and default mode networks implicated by our current study are also functionally linked to the cognitive processes described by Robertson’s. Furthermore, both default mode network and executive control network are known to be modulated by the locus coeruleus-noradrenergic (LC-NE) system (Bär et al, 2016; Minzenberg et al, 2018; Robbins & Arnsten, 2009; Suttkus et al, 2021), which is pivotal to Robertson’s theory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, both the executive control and default mode networks implicated by our current study are also functionally linked to the cognitive processes described by Robertson’s. Furthermore, both default mode network and executive control network are known to be modulated by the locus coeruleus-noradrenergic (LC-NE) system (Bär et al, 2016; Minzenberg et al, 2018; Robbins & Arnsten, 2009; Suttkus et al, 2021), which is pivotal to Robertson’s theory.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both default mode network and executive control network are known to be modulated by the locus coeruleus-noradrenergic (LC-NE) system (Bär et al, 2016;Minzenberg et al, 2018;Robbins & Arnsten, 2009;Suttkus et al, 2021), which is pivotal to Robertson's theory.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies focused on the NE system in SCZ, in particular by combining two or more of the available methods (Table 4), will give us a more complete picture of the disease. Some recent work has been done in this direction (Köhler et al, 2019;Minzenberg et al, 2018). A starting point could be to directly evaluate the triple-networks model (Fig.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…For example, it has been shown that drugs increasing the central NE concentration (e.g., modafinil) lead to more subjective alertness and a better performance on some attention control and working memory measures (Chamberlain & Robbins, 2013). Modafinil has also been shown to be related to the deactivation of the DMN during task performance (Minzenberg et al., 2018). Furthermore, pharmacological manipulations typically depend on baseline levels of arousal, suggesting the importance of tonic NE levels in determining the attentional state (Coull et al., 2004; Smith & Nutt, 1996).…”
Section: Introductionmentioning
confidence: 99%